A Multifunctional Reading Assistant for the Visually Impaired. (6th November 2007) - Mancas-Thillou, Céline; Ferreira, Silvio; Demeyer, Jonathan; Minetti, Christophe; Gosselin, Bernard
Abstract : In the growing market of camera phones, new applications for the visually impaired are nowadays being developed thanks to the increasing capabilities of these equipments. The need to access to text is of primary importance for those people in a society driven by information. To meet this need, our project objective was to develop a multifunctional reading assistant for blind community. The main functionality is the recognition of text in mobile situations but the system can also deal with several specific recognition requests such as banknotes or objects through labels. In this paper, the major challenge is to fully meet user requirements taking into account their disability and some limitations of hardware such as poor resolution, blur, and uneven lighting. For these applications, it is necessary to take a satisfactory picture, which may be challenging for some users. Hence, this point has also been considered by proposing a training tutorial based on image processing methods as well. Developed in a user-centered design, text reading applications are described along with detailed results performed on databases mostly acquired by visually impaired users.